1284. Outcomes by Baseline Pathogens and Susceptibility in the STRIVE Phase 2 Trial of Once-Weekly Rezafungin for Treatment of Candidemia and Invasive Candidiasis Compared with Caspofungin. (31st December 2020) - Thompson, George R; Horcajada, Juan P; Locke, Jeffrey B; Viani, Rolando; Pappas, Peter; Ghannoum, Mahmoud; Sandison, Taylor; Soriano, Alex
Abstract: Background: Rezafungin (RZF) is a novel echinocandin in Phase 3 development for treatment of candidemia and invasive candidiasis (IC) and for prevention of invasive fungal disease caused by Candida, Aspergillus, and Pneumocystis in blood and marrow transplant recipients. This analysis of the completed Phase 2 STRIVE trial (NCT02734862) of RZF treatment was conducted to evaluate outcomes based on baseline pathogen and susceptibility. Methods: In STRIVE, adults (≥ 18 y) with systemic signs and mycological evidence of candidemia and/or IC were randomized to either RZF once weekly or caspofungin (CAS) once daily for ≥ 14 days (Fig. 1). The primary efficacy endpoint was Overall Response (resolution of clinical signs of infection + mycological eradication) at Day 14. For this analysis, outcomes by treatment group were stratified by Candida species and by its in vitro susceptibility (CLSI broth microdilution MIC values; M27-Ed4). Figure 1. Treatment Groups of the Phase 2 STRIVE Trial Results: A total of 196 Candida isolates were recovered from 183 patients across all treatment groups (Fig. 2). C. albicans was the most common species, followed by C. glabrata, C. parapsilosis, and C. tropicalis; non- albicans Candida comprised 54% of all baseline isolates (Fig. 2). Among all clinical isolates, MIC distributions and ranges for RZF were generally lower than or comparable to those for CAS (Table 1). The rate of Overall Response (as defined above) against C. parapsilosis was lower for CAS than for RZF (Table 2). Overall, outcomes by Candida species and MIC did not appear to be affected by MIC values for either RZF or CAS (Table 1). Figure 2. Candida Species Distribution and MIC ranges in the Phase 2 STRIVE Trial (mITT) Table 1. Overall Response Rates (%) for Most Frequently Isolated Candida Species at Baseline by Treatment Group and MIC Values (mITT) Table 2. Overall Response Rates (%) for Most Frequently Isolated Candida Species at Baseline by Treatment Group (mITT) Conclusion: This analysis demonstrated RZF efficacy across multiple Candida species. RZF outcomes were similar to or better than those for CAS regardless of species identified. There was no clear correlation between increased MICs and clinical outcomes although, based on MICs, all isolates exhibited a wild-type in vitro susceptibility profile. These findings from STRIVE, together with future analyses from the ongoing Phase 3 trial of RZF treatment of candidemia and IC (ReSTORE; NCT03667690), will further our understanding of the relationships between MIC values and clinical outcomes in patients with candidemia or IC. Disclosures: Jeffrey B. Locke, PhD, Cidara Therapeutics, Inc. (Employee, Shareholder) Rolando Viani, MD, Cidara Therapeutics, Inc. (Employee, Shareholder) Peter Pappas, MD, SCYNEXIS, Inc. (Consultant, Advisor or Review Panel member, Research Grant or Support) Mahmoud Ghannoum, PhD, Amplyx (Grant/Research Support)Cidara (Grant/Research Support)Scynexis (Consultant, Grant/Research Support) Taylor Sandison, MD, MPH, Cidara Therapeutics, Inc. (Employee, Shareholder)